Penguatan Desa Wisata Berbasis Kampung Iklim: Menuju Terwujudnya Ketahanan Pangan di Desa Pandowoharjo Sleman Yogyakarta - B. Tresno Sumbodo; Sardi Sardi; Sunarya Sunarya; Hermawan Prasetyanto (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
Every household always hopes to have enough food available. While fertile agricultural land is decreasing, food needs increase with increasing population. The use of the yard is expected to help improve food availability for the community.In realizing a climate village tourism village in Pandowoharjo Village, a series of activity programs are designed to be carried out continuously for three years. In Year I of the program, community education activities focused on harvesting and using rainwater for vegetable cultivation in the yard. The design of rainwater harvesting facilities is carried out in the form of IPAH, infiltration wells and dead-end channels (Rorak) in six padukuhan which have been designated as the center of tourism village development namely: Brayut, Temon, Pajangan, Dukuh, Karangtanjung and Plalangan.This method of mentoring the PPDM scheme in Pandowoharjo was carried out in three stages, namely program socialization, training and implementation. The mentoring process is carried out with two approaches, namely theoretical training and skills improvement with practice in the field.The results of the activities in Year I of the PPDM program have benefited partners directly, including: a) Increasing number of people who understand, and have skills in responding to climate change; b) Number of facilities for IPAH, infiltration and rorak wells increased by 15 units; c) The number of people who harvest and utilize rainwater increases by 15KK; d) The number of members of the farmer group of women who use the yard for the cultivation of vegetables with vertikulture and hydroponic systems increases by 20 people.Some achievements that are non-physical such as: network of rainwater harvesters, improvement of knowledge and skills of community members, and pilot cooperation partnerships that integrate several productive economic business groups with BUMDes.